Dupuytren's disease: a localised and accessible human fibrotic disorder - Layton, TB; Williams, L; Nanchahal, J (Cell Press, 2022)
We review the biology of Dupuytren's disease (DD), a common localised fibrotic disorder of the hand. The disease develops through a complex interplay of genetic and environmental factors, and epigenetic signalling. The early-stage disease nodules comprise a complex milieu of stromal and immune cells which interact to promote disease development. Recently, inhibition of tumour necrosis factor (TNF) locally resulted in softening and a decrease in nodule size, potentially controlling disease progression. Unlike fibrotic disorders of the visceral organs, the easy access to tissue in DD patients enables dissection of the cellular landscape and molecular signalling pathways. In addition, the study of DD may have wider benefits in enhancing our understanding of less-accessible fibrotic tissues.